Recent advances in nanomedicines for the treatment of ischemic stroke - Chao Li; Tao Sun; Chen Jiang (Elsevier, 2021)
Ischemic stroke is a cerebrovascular disease normally caused by interrupted blood supply to the brain. Ischemia would initiate the cascade reaction consisted of multiple biochemical events in the damaged areas of the brain, where the ischemic cascade eventually leads to cell death and brain infarction. Extensive researches focusing on different stages of the cascade reaction have been conducted with the aim of curing ischemic stroke. However, traditional treatment methods based on antithrombotic therapy and neuroprotective therapy are greatly limited for their poor safety and treatment efficacy. Nanomedicine provides new possibilities for treating stroke as they could improve the pharmacokinetic behavior of drugs in vivo, achieve effective drug accumulation at the target site, enhance the therapeutic effect and meanwhile reduce the side effect. In this review, we comprehensively describe the pathophysiology of stroke, traditional treatment strategies and emerging nanomedicines, summarize the barriers and methods for transporting nanomedicine to the lesions, and illustrate the latest progress of nanomedicine in treating ischemic stroke, with a view to providing a new feasible path for the treatment of cerebral ischemia.